Product, Price, Promotion and Place Analysis in The Estimation of Pre-Packed Sambal Purchase Decisions: a Research Study on Sambal Sutil Kendil in Surabaya - Irmina Maria Silas (Universitas Ciputra Surabaya, 2022)
This research is aimed at researching and analyzing product variables, prices, promotions and places of the promotional mix that affect, both partially and simultaneously, on the purchasing decision of packaged chili sauce products, with a research study on sambal Sutil Kendil in Surabaya. Statistical analysis using multiple linear regression methods treated using the SPSS 23.0 program. Samples were performed with saturated or census sampling models. Data collection was carried out using questionnaires which used the Likert scale. The questionnaire was distributed in the form of a google form to 113 respondents who were consumers of the Sutil Kendil micro-business. Respondents are domiciled in the geographical area of Greater Surabaya, East Java Province, Central Java Province, Yogyakarta Special Region, Banten Province and the Special Capital Region of Jakarta. The results of this study prove that products, prices, promotions and places have a partial or individual effect, as well as simultaneously or jointly, on the purchase decision of packaged chili sauce products. Variabel place becomes the dominant variable that influences purchasing decisions. The coefficient of determination gives the result that the purchase decision can be explained by the variables of product, price, promotion and place by 68.9%, while 31.1% comes from other variables that are not included in this study.